Review of injury epidemiology in paralympic sports - Carefoot, A.; Willick, S. E. (Adaptive Sports Medicine: A clinical guide, 2024)
Recognizing the rapid evolution of Paralympic sports, which includes an increase in participation, increase in media attention, the addition of new sports, and advancements in technology, is essential to understanding the literature on injury characteristics in Para sports. Interpreting the injury data is complicated by this rapid growth, in addition to the variability in the definition of injury across studies as well as the unique grouping of sports by impairment. The goal of this chapter is to review the current literature on Paralympic sports epidemiology, ultimately in a quest to better care for Para athletes. To better understand possible patterns of injury, this chapter is organized by location, type, and rate of injury with further division between winter and summer sports. Patterns of injury are emerging with the assistance from injury surveillance studies. More recent results have identified significant differences in injury rates between sports and events. However, there is still a need for additional longitudinal, event-specific, sport-specific, and impairment-specific studies, as well as injury reduction interventions.